Analisis Nilai-Nilai Religius Cerita Rakyat ”Ciliwet” dan Rencana Pelaksanaan Pembelajarannya untuk Siswa SMA Tahun Pelajaran 2020/2021 - Trikawati, Trikawati (JEDLISH : Journal Of Education and English Language Teaching, 2022)
The purpose of this research was to find out whether there were religious values in Ciliwet folklore and to obtain an idea of which learning model was appropriate for high school students in the Academic Year of 2018/2019. In this study, the researcher used the descriptive method, which is a method that focuses on solving problems by collecting data, compiling, classifying, analyzing and interpreting, and in the end, it would be described into descriptions in several sentences or paragraphs. The techniques used were observation, interviews, documentations and literature study. The results of the analysis of religious values in the Ciliwet folklore include words which, when classified, were divided into three parts, namely the values of aqidah, the values of shari'a and the values of morality. Aqidah values are values related to the beliefs of God’s creatures to their Creator. Shari'a values are values related to how humans interact with each other and cannot be separated from the true Islamic shari'a thoughts. Further, moral values are values related to behavior, human manners in acting in everyday life.